Peran Kepala Sekolah dalam Upaya Meningkatkan Pendidikan yang Berkarakter dan Berkualitas di SMA Negeri 1 Pulau Morotai - M. Hatta Hi. Saraha (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this school action research is to improve character and quality education. The method used in this study is a qualitative research method with the type of school action research (PTS). with the procedures used in this study, including planning the implementation of action, observation, and reflection. In accordance with the general principles of action research, each stage and cycle is always carried out in a participatory and collaborative manner between researchers and practitioners (principal teachers). The data sources of this research are teachers and students who are involved in activities or activities at SMA Negeri 1 Pulau Morotai. The data of this research is in the form of data about the results of improving quality character education. The data collection procedures used in this study were, 1. Observation, using an observation sheet to measure program achievement activities at SMA Negeri 1 Pulau Morotai. 2. Interview, using an interview guide to find out the opinions or attitudes of students and teachers about character education programs in schools. The data obtained in this study are program planning data, program implementation, and evaluation of character education program evaluations. The research results achieved as indicators of character education achievement are as follows: complying with social rules that apply in a wider environment, respecting religious, cultural, ethnic, racial, and socio-economic diversity within the national scope, increasing achievements in various curricular and extracurricular fields curricular.